Kinetics Study of Gold (III) on Chitosan-Silica Coated Magnetic Material - Dikki Miswanda; Moondra Zubir; Rini Selly; Siti Rahmah; Nuryono Nuryono (Indonesian Journal of Chemical Science and Technology (IJCST), 2022)
A study of the adsorption kinetics of Au(III) ions has been carried out by an adsorbent of silica-chitosan coated magnetic material (BMSK). The BMSK adsorbent was synthesized through a sol-gel process using magnetic materials from iron sand, sodium silicate, and chitosan with 3-chloropropyltrimethoxysilane linker. The adsorption kinetics was studied through batch adsorption system by varying the adsorption time. The number of adsorbed Au(III) ions was calculated based on the difference in metal concentrations before and after adsorption which was analyzed by atomic absorption spectroscopy. The equilibrium of the adsorption of Au(III) ions by the BMSK adsorbent began to occur after the adsorption lasted for 60 minutes. The data shows the interaction of BMSK adsorbent with Au(III) ion following a pseudo order-2 reaction kinetics model with a value of reaction rate constant (k) = 1.199 x 103 g.mg-1.min-1.